2016
DOI: 10.1093/cvr/cvw047
|View full text |Cite
|
Sign up to set email alerts
|

Carfilzomib reverses pulmonary arterial hypertension

Abstract: The addition of anti-tumour agents such as CFZ along with cardioprotectants to currently available vasodilators may be a promising way to improve PAH therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 38 publications
4
74
2
Order By: Relevance
“…We further found that ubiquitin is essential for carfilzomib-induced cell death and some proteins are ubiquitinated in response to carfilzomib treatment. Mass spectrometry identified that one of the proteins ubiquitinated by carfilzomib is MVP, and this was confirmed by immunopecipitation and immunoblotting [17] . The ubiquitination of MVP is promoted in PAs in response to treating rats with PAH by carfilzomib, but not in healthy control rats [17] .…”
Section: Post-translational Modifications Of Mvp (Ubiquitination)mentioning
confidence: 74%
See 4 more Smart Citations
“…We further found that ubiquitin is essential for carfilzomib-induced cell death and some proteins are ubiquitinated in response to carfilzomib treatment. Mass spectrometry identified that one of the proteins ubiquitinated by carfilzomib is MVP, and this was confirmed by immunopecipitation and immunoblotting [17] . The ubiquitination of MVP is promoted in PAs in response to treating rats with PAH by carfilzomib, but not in healthy control rats [17] .…”
Section: Post-translational Modifications Of Mvp (Ubiquitination)mentioning
confidence: 74%
“…Mass spectrometry identified that one of the proteins ubiquitinated by carfilzomib is MVP, and this was confirmed by immunopecipitation and immunoblotting [17] . The ubiquitination of MVP is promoted in PAs in response to treating rats with PAH by carfilzomib, but not in healthy control rats [17] . This ubiquitination of MVP in the remodeled pulmonary vasculature with thickened PA smooth muscle was observed in two different rat models of PAH, namely SU5416 injection plus hypoxia and SU5416 injection plus ovalbumin immunization without changing the expression levels of MVP [17] .…”
Section: Post-translational Modifications Of Mvp (Ubiquitination)mentioning
confidence: 74%
See 3 more Smart Citations